Round and round gets you somewhere: collective cell migration and planar polarity in elongating Drosophila egg chambers - Cetera, Maureen (Curr Opin Genet Dev, 2015)
Planar polarity is a developmental mechanism wherein individual cell behaviors are coordinated across a two-dimensional plane. A great deal of attention has been paid to the roles that the Frizzled/Strabismus and Fat/Dachsous signaling pathways play in this process; however, it is becoming increasingly clear that planar polarity can also be generated through alternate mechanisms. This review focuses on an unconventional form of planar polarity found within the follicular epithelium of the Drosophila egg chamber that helps to create the elongated shape of the egg. We highlight recent studies showing that the planar polarity in this system arises through collective migration of the follicle cells and the resulting rotational motion of the egg chamber.